The Rapid Chloride Migration Test in Assessing the Chloride Penetration Resistance of Normal and Lightweight Concrete - Jorge Pontes; José Alexandre Bogas; Sofia Real; André Silva (Applied Sciences, 2021)
Chloride-induced corrosion has been one of the main causes of reinforced concrete deterioration. One of the most used methods in assessing the chloride penetration resistance of concrete is the rapid chloride migration test (RCMT). This is an expeditious and simple method but may not be representative of the chloride transport behaviour of concrete in real environment. Other methods, like immersion (IT) and wetting–drying tests (WDT), allow for a more accurate approach to reality, but are laborious and very time-consuming. This paper aims to analyse the capacity of RCMT in assessing the chloride penetration resistance of common concrete produced with different types of aggregate (normal and lightweight) and paste composition (variable type of binder and water/binder ratio). To this end, the RCMT results were compared with those obtained from the same concretes under long-term IT and WDT. A reasonable correlation between the RCMT and diffusion tests was found, when slow-reactive supplementary materials or porous lightweight aggregates surrounded by weak pastes were not considered. A poorer correlation was found when concrete was exposed under wetting–drying conditions. Nevertheless, the RCMT was able to sort concretes in different classes of chloride penetration resistance under distinct exposure conditions, regardless of the type of aggregate and water/binder ratio.